Encounters of Despair: Street-Level Bureaucrat and Migrant Interactions in Sweden and Switzerland - Borrelli, Lisa (Anthropologica, 2021)
Encounters between street-level bureaucrats and the so-called “client of the state” – here the migrant individual with precarious legal status – are characterized by great power imbalances. The dependency relationships that emerge out of public administrative encounters need to be understood as spaces of continuous asymmetrical negotiations. Emotions play a crucial role, not only as a translation of how migrants and bureaucrats mutually shape, contest, and reproduce migration control, but also as a strategic component and a tool for negotiation. Supported by ethnographic data from a Swiss Cantonal Migration Office and a Swedish Border Police Unit, collected between 2016 and 2017, I argue that emotions interweave all migrant-bureaucrat interactions. Their analysis discloses not only the emotional labour of migration enforcement, but also how it is translated into bureaucratically enacted practices, which include physical force, vocal exchanges, documents and spatial means, leading to what Walters (2006) coined “political economies of violence” (438).